Serum ghrelin, IL-6 and TNF-? levels in patients with chronic obstructive pulmonary disease - Deveci, Yasemin; Deveci, Figen; Ilhan, Nevin; Karaca, Ilgin; Turgut, Teyfik; Muz, Mehmet Hamdi (Turkish Assoc Tuberculosis & Thorax, 2010)
It is determined that endocrine factors can play role on cachexia in chronic obstructive pulmonary disease (COPD). High levels of ghrelin is reported in cachectic COPD cases but its' relation couldn't shown statistically. In our study, it is aimed to detect serum ghrelin levels in COPD, its' relation with proinflammatory cytokines and whether serum ghrelin is associated with cachexia. Sixty stable COPD patients and 15 healthy volunteers were included in the study. COPD patients were divided into two groups, cachectic and normal weight, according to their body mass index. Spirometric assessments were performed and serum tumor necrosis factor-alpha (TNF-alpha), interleukin-6 (IL-6) and ghrelin levels were measured in all cases. When COPD patients were compared with control group; serum ghrelin levels were statistically lower, TNF-alpha and IL-6 levels were statistically higher in COPD group. For cachectic COPD patients; serum ghrelin levels were statistically lower and IL-6 levels were statistically higher, compared with normal weight COPD patients. Although, serum TNF-alpha levels were higher for cachectic COPD patients; these levels were not significant. Positive correlation between serum ghrelin levels and body mass index was detected in patients with COPD. As a result; it is thought that increased proinflammatory cytokins and decreased serum active ghrelin levels may contribute to the development of weight loss.
Kronik obstrüktif akci?er hastali?i olan olgularda serum grelin, IL-6 ve TNF-? düzeyleri
Keywords: COPD; ghrelin; TNF-alpha; IL-6